Studi Variabilitas Isotop Airhujan Sebagai Fungsi Elevasi untuk Mendapatkan Merapi Meteoric Water Line MMWL - Agus Budhie Wijatna; S Sudarmadji; S Sunarno; Heru Hendrayana (Forum Teknik, 2013)
Theoretically environmental isotopic compositions ofprecipitation decrease with increasing altitude. Linear regression analysis was applied to environmental isotopic compositions (δ18O, δ2H) data on 15 precipitation samples collected along an altitudinal 126 to 1260 m.asl from November 2011 to February 2012 to determine the local meteoric water line for southern slope of mount Merapi. Merapi meteoric water line (MMWL) is an equation that describes the relationship between isotopic compositions of precipitation with altitude. This study was completed as part of a larger research of the groundwater dynamics studies using natural isotopes for southern slope of mount Merapi.Isotopic compositions of precipitation samples were measured using Liquid-Water Stable Isotope Analyzer LGR DLT-100 at the Center for the Application of Isotopes & Radiation Technology Laboratory, National Nuclear Energy Agency (BATAN), Jakarta. Regression results for the precipitation samples for southern slope of mount Merapi yielded a MMWL defined by the equation δ2H=8.332 δ18O+15.068(r2 =0,998); the change of isotopic compositions in precipitation with altitude of about -1.2%d100m for deuterium and -0. 1 %dl 00m for oxygen-18.This equation will be useful as reference for hydrological dynamics studies on the southern slope of mount Merapi that use isotopes of 2H and 18O to trace sources of ground-water recharge, to evaluate mixing of sea-water and groundwater, to analyze groundwater-mineral exchange, and to analyze many other groundwater contamination problems.Keywords: precipitation, isotope ratio, isotopic composition, m.asl, MML .